2014
DOI: 10.1016/j.sleep.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Increases in duration of first uninterrupted sleep period are associated with improvements in PSQI-measured sleep quality

Abstract: Objective Urology clinical trials assessing bladder function have relied on the self-reported duration of the first uninterrupted sleep period (FUSP) as a proxy outcome for sleep, but the relationship between this measure and more conventional self-reported measures of sleep is unknown. In this study, we examined the association between changes in FUSP and a widely used self-reported measure of sleep, the Pittsburgh Sleep Quality Index (PSQI). Methods We conducted post-hoc (secondary) analyses of unpublished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Thus, DUS may explain the relationship between NP and sleep quality, and increasing DUS through decreasing NPi could be a potential target for improving sleep quality and decreasing nocturia burden among older adults. 22, 23 These findings suggest a bidirectional relation between sleep and nocturia. So, too, does our earlier study, which revealed that behavioral approach to insomnia reduced nocturia.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, DUS may explain the relationship between NP and sleep quality, and increasing DUS through decreasing NPi could be a potential target for improving sleep quality and decreasing nocturia burden among older adults. 22, 23 These findings suggest a bidirectional relation between sleep and nocturia. So, too, does our earlier study, which revealed that behavioral approach to insomnia reduced nocturia.…”
Section: Discussionmentioning
confidence: 75%
“…-Delayed sleep phase syndrome (Skene et al, 1999) -Sleep-onset insomnia (Wang-Weigand et al, 2009) -Non-24 h sleep/wake disorder -SW schedule disorder (Roth, 2012) -Smith-Magenis syndrome (Chen et al, 2015) -Delirium (Furuya et al, 2012) -Peptic ulcer disease (Moore & Merki, 1997) -Depression, mania, seasonal affective disorder and seasonal affective bipolar disorder (Dallaspezia et al, 2015;Geoffroy et al, 2015;Klemfuss & Kripke, 1989;Melrose, 2015;Salgado-Delgado et al, 2011) -Nocturnal asthma (Smolensky & D'Alonzo, 1997;) -AI (Chan & Debono, 2010;Debono et al, 2009;Ekman et al, 2014;Johannsson et al, 2009;Quinkler et al, 2015) -Nocturia (Bliwise et al, 2014;Ebell et al, 2014;Miller, 2000;Moon et al, 2004) -Sleep-time non-dipping and rising 24 h BP patterns, that is nocturnal hypertension Hermida et al, 2011aHermida et al, , b, c, 2013cPortaluppi & Smolensky, 2010;Smolensky et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…In responsive patients, this chronotherapeutic strategy restores toward normal the circadian rhythm of H 2 O diuresis with consequent beneficial effect on sleep quality and the sleep/wake 24 h cycle (Bliwise et al, 2014;Ebell et al, 2014;Miller, 2000;Moon et al, 2004).…”
Section: Nocturiamentioning
confidence: 99%
“…Items were administered based on an open-ended format (e.g., usual bedtime) or a 4-point Likert scale (e.g., overall sleep quality during the past month: very good, fairly good, fairly bad, and very bad). Using the traditional scoring, items were recoded and used to compute seven sleep components (e.g., subjective sleep quality, use of sleep medications), which then were summed to yield one global score (Range: 0–12) with higher scores indicating poorer sleep quality (17, 39, 40). …”
Section: Methodsmentioning
confidence: 99%